2019
DOI: 10.1002/cnma.201900241
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Properties of Zn−Ag−In−Te Nanocrystals with High Energy Photon Excitation

Abstract: Multinary nanocrystals (NCs) of I‐III‐VI‐based semiconductors with less toxicity have attracted much attention for the fabrication of efficient light‐energy conversion systems. Here we report unique photoelectrochemical properties of ZnTe−AgInTe2 solid solution (ZAITe) NCs with a controllable energy gap in near‐IR region. The photoelectrochemical behavior of ZAITe NCs immobilized on an ITO electrode with a thickness of less than one monoparticle layer, resembling a p‐type semiconductor photoresponse, was remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It was reported in our previous paper that multiple excitons could not be generated by the absorption of a single 3.1 eV-photon with a ZAITe NC despite an hn/E g ratio of 2.44. 34 Thus, the present results indicated that hot electrons, excited to a higher level with higherenergy photon absorption, could be more efficiently extracted with MV 2+ (Fig. 3c).…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…It was reported in our previous paper that multiple excitons could not be generated by the absorption of a single 3.1 eV-photon with a ZAITe NC despite an hn/E g ratio of 2.44. 34 Thus, the present results indicated that hot electrons, excited to a higher level with higherenergy photon absorption, could be more efficiently extracted with MV 2+ (Fig. 3c).…”
Section: Resultssupporting
confidence: 60%
“…We previously reported that the level of the conduction band minimum (E CB ) of ZAITe NCs was À1.3 V vs. Ag/AgCl for the composition of x ¼ 0.75. 34 Since the redox potential of MV 2+ /MVc + , À0.65 V vs. Ag/AgCl, 35 was more positive than the E CB of ZAITe NCs used, excited electrons in the present ZAITe NCs were able to efficiently transfer to MV 2+ .…”
Section: Methodsmentioning
confidence: 86%
See 3 more Smart Citations